Biased Visuospatial Attention in Cervical Dystonia. (9th August 2017) - Chillemi, Gaetana; Formica, Caterina; Salatino, Adriana; Calamuneri, Alessandro; Girlanda, Paolo; Morgante, Francesca; Milardi, Demetrio; Terranova, Carmen; Cacciola, Alberto; Quartarone, Angelo; Ricci, Raffaella
Abstract: Objectives: There is increasing evidence of non-motor, sensory symptoms, mainly involving the spatial domain, in cervical dystonia (CD). These manifestations are likely driven by dysfunctional overactivity of the parietal cortex during the execution of a sensory task. Few studies also suggest the possibility that visuospatial attention might be specifically affected in patients with CD. Therefore, we asked whether non-motor manifestations in CD might also comprise impairment of higher level visuospatial processing.Methods: To this end, we investigated visuospatial attention in 23 CD patients and 12 matched healthy controls (for age, gender, education, and ocular dominance). The patients were identified according to the dystonia pattern type (laterocollis vs . torticollis). Overall, participants were right-handers, and the majority of them was right-eye dominant. Visuospatial attention was assessed using a line bisection task. Participants were asked to bisect horizontal lines, using their right or left hand.Results: Participants bisected more to the left of true center when using their left hand to perform the task than when using their right hand. However, overall, torticollis patients produced a significantly greater leftward deviation than controls.Conclusions: These data are consistent with preliminary findings suggesting the presence of biased spatial attention in patients with idiopathic cervical dystonia. The presence of an attentional bias in patients with torticollis seem to indicate that alterations of attentional circuits might be implicated in the pathophysiology of this type of CD. ( JINS, 2018, 24, 23–32)